(untitled) (Research, Society and Development, 2022)
In contemporary times, the Human Immunodeficiency Virus infection is still a serious public health problem, due to the consequences and global impacts caused, as well as for maintaining growth rates of the virus infection. Furthermore, it can be said that women living with HIV and AIDS are particularly stigmatized, given that the confirmation of the diagnosis of the virus imposes several changes on the woman. The objective of this study is to carry out an integrative literature review that exposes results in scientific databases about nurses’ care for pregnant women with HIV-1; This is an integrative literature review approach. The databases were the VHL, BDTD, LILACS and PUBMED. The publications were with a time frame of the last seven years, from 2014 to 2020. It is concluded that the experience of motherhood lived with the HIV virus has an outcome of acceptance and practices of maternal and child care directly linked to the nurse. Through knowledge on the subject, it is possible for the pregnant woman to have better prevention of diseases and clinical management, starting from teaching actions, such as counseling and guidance on the experience of HIV-positive motherhood. The nurse is at the forefront of care and assistance to pregnant women throughout the gestational period, through their knowledge, this professional is able to help in the care of the pregnant woman and the baby that is on the way.